2020
DOI: 10.1111/1462-2920.15114
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of the rice microbial community of the Chinese centuries‐old Honghe Hani rice terraces system

Abstract: Summary The Honghe Hani rice terraces system (HHRTS) is a traditional rice cultivation system where Hani people cultivate remarkably diverse rice varieties. Recent introductions of modern rice varieties to the HHRTS have significantly increased the severity of rice diseases within the terraces. Here, we determine the impacts of these recent introductions on the composition of the rice‐associated microbial communities. We confirm that the HHRTS contains a range of both traditional HHRTS landraces and introduced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 85 publications
0
7
0
Order By: Relevance
“…Domestication has been shown to alter the diversity of microbes in the rhizosphere of crops such as corn [ 45 ], tomato [ 46 ], wheat [ 47 ], and rice [ 48 , 49 ]. Chang et al [ 50 ] compared the bacterial communities of wild and domesticated rice genotypes and found that Frankiaceae was enriched in the rhizosphere of cultivated Oryza sativa but absent from the rhizosphere of wild Oryza rufipogon .…”
Section: Discussionmentioning
confidence: 99%
“…Domestication has been shown to alter the diversity of microbes in the rhizosphere of crops such as corn [ 45 ], tomato [ 46 ], wheat [ 47 ], and rice [ 48 , 49 ]. Chang et al [ 50 ] compared the bacterial communities of wild and domesticated rice genotypes and found that Frankiaceae was enriched in the rhizosphere of cultivated Oryza sativa but absent from the rhizosphere of wild Oryza rufipogon .…”
Section: Discussionmentioning
confidence: 99%
“…For example, in the Chinese traditional Hani rice terraces system, three distinct rice genetic clusters were categorized using a genotyping by sequencing approach, while two main groups were initially expected based on farmer nomenclature. In addition, two rice fields planted with a variety bearing the same name were genetically distinct (Alonso et al, 2019(Alonso et al, , 2020.…”
Section: What To Sample?mentioning
confidence: 99%
“…The long history of rice cultivation might contribute to the accumulation of rice varieties in Dai's distribution areas [33]. Regional rotation phenomenon of rice seed was common for Hani, as relatives and friends were used to exchange rice seeds, which would not only help to prevent the rice aging but also preserve the traditional rice germplasm resources [34]. Likewise, Lahu and Blang also had a long history of rice cropping, with religious traditions to conserve the rice varieties, which enriched their diversity of rice varieties to a certain extent [35,36].…”
Section: Eco-environmental Adaptability Of Ethnic Groupsmentioning
confidence: 99%